(untitled) (Medico Legal Update, 2021)
The vulvovaginitis candidiasis is often associated with biofilm formation by Candida albicans and using of antifungal agents against C. albicans biofilms is urgently needed. Microtiter plate assay using crystal violet was used for detection the ability of Candida albicans to form biofilm and the microtiter broth dilution method was used for determination the minimum inhibitory concentrations (MICs). Out of 42 Candida albicans isolated from vulvovaginitis, 37 (88%) can produce biofilm at the varying degrees. Twenty-eight (75.7%) isolates could form a strong biofilm. The results of minimum inhibitory concentrations (MICs) of Nystatin, Aspirin and EDTA (Ethylenediaminetetraacetic acid) against 28 C. albicans isolates which formed the strong biofilm, revealed that range of concentrations of Nystatin were (6.25-100 µg/ml), while the MICs of aspirin and EDTA were more than 1000 µg/ml. It was obvious that the Nystatin had the inhibitory activity at the concentrations 6.25 and 12.5 µg/ml. The highest antibiofilm activity by Nystatin were demonstrated at the subinhibitory concentration 50 ?g/ml with biofilm eradication percent (75.80%), while the lowest antifungal effect (2.86-10.70%) was at very low concentrations (3.125-6.25 ?g/ml). Also, there was an obvious biofilm eradication of Aspirin and EDTA at the concentrations 500 and 1000 ?g/ml but the effect of aspirin at the concentration 1000 ?g/ml (70.51%) is more than EDTA (60.12%) in contrast with the concentration 500 ?g/ml, it was found that the effect of EDTA (51.29%) is more than aspirin (34.25%). In conclusion, the present study highlights the role of Aspirin and EDTA as antibiofilm agents when used with Nystatin which have the ability to inhibit the growth of C. albicans in patients with vulvovaginitis.